Recent advances in enzyme-related biomaterials for arthritis treatment - Liu, Xin-Hao; Ding, Jia-Ying; Zhu, Zhi-Heng; Wu, Xi-Chen; Song, Yong-Jia; Xu, Xiao-Ling; Ding, Dao-Fang (Frontiers in Chemistry, 2022)
Arthritis is a group of highly prevalent joint disorders, and osteoarthritis (OA) and rheumatoid arthritis are the two most common types. The high prevalence of arthritis causes severe burdens on individuals, society and the economy. Currently, the primary treatment of arthritis is to relieve symptoms, but the development of arthritis cannot be effectively prevented. Studies have revealed that the disrupted balance of enzymes determines the pathological changes in arthritis. In particular, the increased levels of matrix metalloproteinases and the decreased expression of endogenous antioxidant enzymes promote the progression of arthritis. New therapeutic strategies have been developed based on the expression characteristics of these enzymes. Biomaterials have been designed that are responsive when the destructive enzymes MMPs are increased or have the activities of the antioxidant enzymes that play a protective role in arthritis. Here, we summarize recent studies on biomaterials associated with MMPs and antioxidant enzymes involved in the pathological process of arthritis. These enzyme-related biomaterials have been shown to be beneficial for arthritis treatment, but there are still some problems that need to be solved to improve efficacy, especially penetrating the deeper layer of articular cartilage and targeting osteoclasts in subchondral bone. In conclusion, enzyme-related nano-therapy is challenging and promising for arthritis treatment.